The Values of Islamic Education in Surah Ar-Rum Verse 21 and Its Implications Community Life The Bataraguru Village of Baubau City - Abdul Rahim; Muhammad Ridwan; Rahmah Rahmah (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
The purposes of this study are: (1) To find out the values ​​of Islamic education in surah Ar-Rum verse 21 in the life of the Bataraguru sub-district, Baubau city; (2) To find out the implications of surah Ar-Rum verse 21 in the life of the Bataraguru village, Baubau city. The research approach used in this research is qualitative research. The technique of collecting data is carried out by observing, interviewing, and documenting. The procedure for collecting the data was by conducting research directly to the location that was used as the research target as well as collecting data by quoting the opinions of experts, then when the data was collected the writer carried out a qualitative descriptive analysis. Every research activity certainly has a population and sample. As for the population of this study were 95 people, while the sample was 10 people. The results of the study show that: (1) The people of the Bataraguru subdistrict, Baubau city, who are married already know and understand what is contained in surah Ar-Rum verse 21; (2) The implication is that the Bataraguru sub-district community, Baubau city, in general, has implemented what is contained in surah Ar-Rum verse 21. They already know and always try to apply what Sakinah family is, Mawaddah wa Rahmah.